SWOT analysis of Sodamolek virgin coconut oil (VCO) in West Amarasi district, Kupang Regency - Adolfina Kudji Lede; Imanuel Talan; Surya Setyawan (Universitas Nusa Cendana, 2026)
This study analyzes the internal and external factors influencing the development of the “Sodamolek” Virgin Coconut Oil (VCO) enterprise through a SWOT framework to formulate sustainable business development strategies. Originating as a community-based economic empowerment initiative managed by a church congregation in Fedok Lenaoen under the Northwest Rote Classis and subsequently expanded to West Amarasi, the enterprise was established to address persistent challenges related to low household income and economically motivated crime in local communities. Employing a qualitative descriptive approach, the study identifies the enterprise’s primary strengths as its use of natural, chemical-free raw materials and its affordable pricing strategy. Significant opportunities were also identified, including growing public awareness of health and wellness products and the potential for expansion into international markets, particularly in the Netherlands. The findings suggest that the most appropriate development strategy involves strengthening access to raw materials, expanding product diversification into value-added products such as lotions, facial masks, and instant porridge, and addressing existing weaknesses related to packaging innovation and workforce capacity development. Beyond its commercial achievements, the Sodamolek initiative has generated meaningful socio-economic benefits by creating local employment opportunities, increasing household income, and contributing to community welfare. The study highlights how faith-based economic empowerment initiatives can support local development objectives and demonstrates the potential of community-driven entrepreneurship to promote inclusive economic growth and social stability in rural regions of East Nusa Tenggara. Keywords: Business Development Strategy; Church Initiative; Community Empowerment; Economic Improvement; SWOT Analysis; Virgin Coconut Oil (VCO)